ANALISIS PROSES INOVASI PERENCANAAN PRODUK BARU (Studi Pada Perusahaan Kurir dan Kargo PT. Citosarana Jasapratama) - Edwin Sutadipraja (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
This research aimed to examine the innovation process executed by PT. CitosaranaJasapratama (Cito) in developing a new service, so called the Mailing Control Management and toexamine the success factors behind this new service. The result showed that Cito has executedseveral process in developing their new service. Firstly, Cito analyze the customer’s value to havebetter understanding abaout their preferences to this new service, then, they studied whether thisnew service still has promising market. They continue the processes by generating ideas about howthis new service should be designed and selecting the most promising idea. Cito undergone athorough business analysis to see wheter this new service profitable to the company, then, they C tothe market. The success factors of this new service can be seen from the very begining stage of theirnew service development. Cito has been successful to be effective in developing their new serviceby having excellence understanding about their customer need prior the cration of this new service,they alsosucceeded to be efficient by matching their capability with the value opportunities, and thelast, they have a unique commercialization methode in offering thid new service to the customer.